Predictors of pain during nasopharyngeal swab among Covid-19 suspected cases in Central Malacca, Malaysia - Ismail, Fatin; Zulkefli, Nor Afiah Mohd; Radzali, Mohd Hafiz Idlan (Universiti Putra Malaysia, 2024)
Introduction: Nasopharyngeal swab (NPS) is the screening tool for Coronavirus Disease 2019 (COVID-19). It is a painful procedure that leads people to refuse it. Since there was no pain evaluation conducted, this study is to examine the pain prevalence and its predictors during NPS among COVID-19 suspected cases at Central Malacca drive-through screening centre. Materials and methods: A cross-sectional study was conducted among 365 screened respondents, selected through simple random sampling in May 2021. The pain category was divided into clinically significant pain (CSP) and Non-CSP using the Ministry of Health Pain Scale. Independent variables were the sociodemographic factors, frequency of NPS, operators' experience score and swab tip type. Data was collected using validated, self-administered Google form questionnaire, blasted via WhatsApp and the analysis was done using IBM SPSS software version 26. Results: The response rate was 86.4% with 53.5% reported having CSP. Binary Logistic Regression revealed frequent NPS procedures (OR= 1.18, 95% CI 1.01-1.38, p=0.040) and the nylon-flocked swab tip (OR= 2.08, 95% CI 1.24-3.49, p=0.006) have higher odds of CSP. Operator with more experience score is less likely to cause CSP to respondents (OR = 0.94, 95% CI 0.89-0.99, p <0.048). The predictors of CSP during NPS among COVID-19 suspected cases are of higher frequency of NPS and nylon-flocked swab tip. Increase operators' experience score is the protective factor for CSP. Conclusion: The painless saliva self-testing modality screening for COVID-19 is highly recommended.